A Case Report of Neuroleukemiosis Detected on FDG PET Scan in a Patient of Mixed Phenotype Acute Leukemia Post Bone Marrow Transplantation in Remission - Soundararajan, Ramya; Yadav, Archana; AVS, Anil Kumar; Jangir, Hemlata (World Journal of Nuclear Medicine, 2024)
Neuroleukemiosis, an exceedingly rare manifestation of leukemia, is defined as peripheral nerve infiltration by leukemic cells. The typical clinical presentation is with peripheral neuropathy and/or chloromatous masses. The diagnosis of this condition is quite challenging, as symptoms usually appear in patients during remission and there are no other signs of relapse. The diagnosis is supported with electrophysiologic testing and imaging and finally established with histopathology and immunophenotyping. We present a case of multineuritis in a patient with mixed phenotype acute leukemia during remission post allogeneic hematopoietic stem cell transplant, where inflamed thickened nerves were detected on positron emission tomography/computed tomography imaging with fluorine-18 fluorodeoxyglucose. A diagnosis of neuroleukemiosis was established via biopsy and immunophenotyping. The literature is reviewed regarding this interesting and rare clinical condition.
Keywords: 18F-FDG PET/CT; peripheral nerve; acute leukemia; extramedullary; neuroleukemiosis